2023
DOI: 10.1038/s41598-022-26813-8
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular evidence of hookworms in public environment of Bangladesh

Abstract: Accurate diagnosis by precise identification of causative agents is essential for the effectiveness of any control interventions. Despite high zoonotic potential, available literature on hookworms in Bangladesh is still scarce and nonspecific. The objective of this study was to determine the occurrence of hookworms in public locations across northeastern Bangladesh (Sylhet metropolitan area) using integrated parasitological and molecular assays. A total of 130 samples (80 soil and 50 environmental canine feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several studies have reported soil contamination with Ancylostoma spp. in public places, universities, schools, clubs and beaches ( Gallina et al, 2011 ; Rocha et al, 2011 ; Marques et al, 2012 ; Ribeiro et al, 2013 ; Sprenger et al, 2014 ; Leon et al, 2020 ; Silva et al, 2020 ; Lee et al, 2021 ; Mello et al, 2022 ; Nath et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported soil contamination with Ancylostoma spp. in public places, universities, schools, clubs and beaches ( Gallina et al, 2011 ; Rocha et al, 2011 ; Marques et al, 2012 ; Ribeiro et al, 2013 ; Sprenger et al, 2014 ; Leon et al, 2020 ; Silva et al, 2020 ; Lee et al, 2021 ; Mello et al, 2022 ; Nath et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal nematodes are known to be agents that can potentially interfere with animal health and the general welfare of society in various parts of the world. Gastrointestinal nematode infection is a significant obstacle in animal health and public health (Beugnet et al 2014;de Mello et al 2022;Martínez-Sotelo et al 2022;Nath et al 2022;Tadege et al 2022;Nath et al 2023). Cats (Felis catus Linnaeus, 1758) from private households, kennels, and feral cats can be infected by gastrointestinal nematodes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the resistance of gastrointestinal nematodes to anthelmintics in animals has been reported worldwide, and single and multiple anthelmintic resistance is of most significant concern worldwide (Castro et al 2019;Kitchen et al 2019;Zekarias and Toka 2019;Fissiha and Kinde 2021;Castro et al 2021;O'Halloran 2021). Some anthelmintic resistance poses a serious threat to animals and society and is very prevalent in countries such as the United States (Castro et al 2019(Castro et al , 2021, China (Wang et al 2017), and Bangladesh (Nath et al 2023).…”
Section: Introductionmentioning
confidence: 99%